2017
DOI: 10.1155/2017/5165916
|View full text |Cite
|
Sign up to set email alerts
|

Functional Profile Evaluation of Lactobacillus fermentum TCUESC01: A New Potential Probiotic Strain Isolated during Cocoa Fermentation

Abstract: The use of intestinal probiotic bacteria is very common in the food industry and has been the focus of the majority of research in this field. Yet in recent years, research on extraintestinal microorganisms has greatly increased due to their well-known potential as probiotics. Thus, we studied a strain of Lactobacillus fermentum (TCUESC01) extracted from fermenting cocoa. First, we examined the impact of pH on the growth of this strain and studied its survival under conditions similar to those of the human gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Most of the probiotics available on the market have human origin, due to the concept that (it was expected) their action would be accentuated in organisms of the same species from which the strain was primarily isolated. However, new studies have shown that microorganisms of extraintestinal origin, isolated from plants and fermented foods, exhibit promising effects in the treatment and prevention of numerous diseases [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the probiotics available on the market have human origin, due to the concept that (it was expected) their action would be accentuated in organisms of the same species from which the strain was primarily isolated. However, new studies have shown that microorganisms of extraintestinal origin, isolated from plants and fermented foods, exhibit promising effects in the treatment and prevention of numerous diseases [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interest in searching for new strains with probiotic potential has risen in the industrial and scientific sectors mainly due to the market demand for functional foods and therapeutics with lesser side effects and because of the numerous benefits attributed to these microorganisms [ 9 , 15 ]. The role of LAB in cocoa fermentation has not been fully clarified, but the diversity of bacteria involved in this process makes this process/product a promising source for isolation of the prospecting strains for biotechnology applications [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…All isolates were screened for their susceptibility to ampicillin (10 μg), amikacin (30 μg), vancomycin (30 μg), gentamicin (10 μg), kanamycin (30 μg), clindamycin (2 μg), rifampicin (5 μg), streptomycin (30 μg), tetracycline (30 μg), erythromycin (15 μg), ciprofloxacin (5 μg), chloramphenicol (30 μg). After 48 h incubation in anaerobic conditions at 37°C, the diameter of the inhibition zone was measured and interpreted as susceptible (S), intermediate (I), or resistant (R) according to [45]. For ampicillin (≤16 mm) and rifampicin (≤16 mm), breakpoints recommended for Enterococcus spp.…”
Section: Resistance To Antibioticsmentioning
confidence: 99%
“…Daily ingested by humans playing significant roles as health-promoting probiotics which is the most important point, to improve general health and protect from different kinds of illness [3][4][5][6]. Also used as production of food and feed throughout the world [7][8][9][10][11] because widely used in the food industry for the production and the preservation of fermented products such as wholegrain sourdough bread or sourdough fermentation [12,13]. Daily consumption of dairy yogurt having Lactobacillus paracasei, and heattreated Lactobacillus plantarum possibly is successful alternative to improve immune function by enhancing IFN-γ concentration and NK cell function [14].…”
Section: Introductionmentioning
confidence: 99%